Evolutionary Computation in Combinatorial Optimization 10th European Conference, EvoCOP 2010, Istanbul, Turkey, April 7-9, 2010. Proceedings - Cowling, Peter; Merz, Peter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 10th European Conference on Evolutionary Computation in Combinatorial Optimization, EvoCOP 2010, held in Instanbul, Turkey, in April 2010. The 24 revised full papers presented were carefully reviewed an selected from 69 submissions. The papers present the latest research and discuss current developments and applications in metaheuristics - a paradigm to effectively solve difficult combinatorial optimization problems appearing in various industrial, economical, and scientific domains. Prominent examples of metaheuristics are evolutionary algorithms, simulated annealing, tabu search, scatter search, memetic algorithms, variable neighborhood search, iterated local search, greedy radomized adaptive search procedures, estimation of distribution algorithms and ant colony opitmization.
Dual Sequence Simulated Annealing with Round-Robin Approach for University Course Timetabling -- Heuristic and Exact Methods for the Discrete (r |p)-Centroid Problem -- On the Benefit of Sub-optimality within the Divide-and-Evolve Scheme -- A Real-Integer-Discrete-Coded Differential Evolution Algorithm: A Preliminary Study -- Fitness Distance Correlation and Search Space Analysis for Permutation Based Problems -- A Genetic Algorithm to Minimize Chromatic Entropy -- Evolutionary Approaches to the Three-dimensional Multi-pipe Routing Problem: A Comparative Study Using Direct Encodings -- A Tabu Search Heuristic for Point Coverage, Sink Location, and Data Routing in Wireless Sensor Networks -- Ant Colony Optimization for Tree Decompositions -- Iterated Local Search with Path Relinking for Solving Parallel Machines Scheduling Problem with Resource-Assignable Sequence Dependent Setup Times -- Enhancing a Tabu Algorithm for Approximate Graph Matching by Using Similarity Measures -- Characterizing Fault-Tolerance of Genetic Algorithms in Desktop Grid Systems -- The Office-Space-Allocation Problem in Strongly Hierarchized Organizations -- A Study of Memetic Search with Multi-parent Combination for UBQP -- Bicriteria Scheduling Problem on the Two-Machine Flowshop Using Simulated Annealing -- A Memetic Algorithm for Workforce Distribution in Dynamic Multi-Skill Call Centres -- Geometric Generalization of the Nelder-Mead Algorithm -- Guided Ejection Search for the Pickup and Delivery Problem with Time Windows -- An Evolutionary Algorithm Guided by Preferences Elicited According to the ELECTRE TRI Method Principles -- Multilevel Variable Neighborhood Search for Periodic Routing Problems -- Enhancing Genetic Algorithms by a Trie-Based Complete Solution Archive -- A New Primal-Dual Genetic Algorithm: Case Study for the Winner Determination Problem -- Local Search Algorithms on Graphics Processing Units. A Case Study: The Permutation Perceptron Problem -- Efficient Cycle Search for the Minimum Routing Cost Spanning Tree Problem.
Keywords: Computer science; Computer software; Computational complexity; Computer vision; Optical pattern recognition; Computer Science; Algorithm Analysis and Problem Complexity; Computation by Abstract Devices; Pattern Recognition; Image Processing and Computer Vision; Discrete Mathematics in Computer Science